Trends in Prevalence and Incidence of Epilepsy and Drug-Resistant Epilepsy in Children: A Nationwide Population-Based Study in Korea - Jooyoung Lee; Arum Choi; Sukil Kim; Il Han Yoo (MDPI AG, 2024)
Population-based data on drug-resistant epilepsy (DRE) are lacking. This retrospective study aimed to determine the prevalence and incidence of pediatric epilepsy and DRE in South Korea using health insurance claims data from the Health Insurance Review and Assessment Service (2013-2022). Epilepsy and DRE prevalence and incidence in children <18 years old were estimated over time and by age and sex. Results showed that the age-standardized prevalence and incidence rates of epilepsy increased. The age-standardized prevalence rate of DRE increased, while the age-standardized incidence rate remained unchanged. The standardized prevalence rate of DRE was 0.26 per 1000 persons, and the average standardized incidence rate of DRE was 0.06 per 1000 persons. The prevalence rate of DRE gradually increased with age, with age 0 demonstrating the highest incidence rate. The prevalence of generalized DRE was the highest across all ages, and incidence was the highest at 0 years. Conversely, the incidence of focal DRE did not change with age. Our study revealed a stable incidence rate of DRE in Korea, despite increased prevalence. DRE incidence was the highest in the first year of life, with the generalized type being the most prevalent.